2015
DOI: 10.1111/jicd.12174
|View full text |Cite
|
Sign up to set email alerts
|

Dental treatment under general anesthesia for special‐needs patients: analysis of the literature

Abstract: The aim of the present review was to identify the studies published on dental treatment under general anesthesia for special-needs patients. A comprehensive search of the reported literature from January 1966 to May 2012 was conducted using PubMed, Medline, and Embase. Keywords used in the search were "dental treatment under general anesthesia", "special-needs patients", "medically-compromised patients", and "children", in various combinations. Studies published only on dental treatment under general anesthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
66
1
8

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(75 citation statements)
references
References 22 publications
0
66
1
8
Order By: Relevance
“…This argument has been used to justify an increase in restorative procedures, mainly fillings, such as that detected in this study starting the first 6‐year period. This trend has led to a predominance of restorative versus surgical treatments in the series published to date …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This argument has been used to justify an increase in restorative procedures, mainly fillings, such as that detected in this study starting the first 6‐year period. This trend has led to a predominance of restorative versus surgical treatments in the series published to date …”
Section: Discussionmentioning
confidence: 99%
“…3,4 Intellectual disability and behavior disorders continue to be the most common systemic diagnoses among patients who undergo treatment under GA. 5 There is virtually unanimous agreement in the literature in considering caries as the main indication for performing treatment, 6 followed by periodontal disease. 7 We detected significant disparity among the published studies in terms of the dental procedures performed, 8 although extractions generally predominated, 9 which can be explained by the advanced state of tooth decay at the time of the operation and in many cases by the inability to follow appropriate postoperative maintenance. 8 Recent studies have reported a considerable increase in restorative treatments.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…In this particular case of a special needs patient, ceramic veneer by CAD/CAM was the best solution in terms of longevity, aesthetics, and prevention of caries . It has been shown that restorative procedures are often affected by problems of attendance and high failure rates before 5 years . For our young patient, direct composite restoration of an incisal edge would not have been a good solution because cooperation was insufficient to enable an aesthetic and lasting rehabilitation to be made, specifically in a patient who chewed strongly on any object inserted in her mouth.…”
Section: Discussionmentioning
confidence: 99%